PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DAN WORD OF MOUTH PADA HOSPITAL NASIONAL GUIDO VALADARES DILI TIMOR LESTE - Wuda, Roslina Lali; Sri Suprapti, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.11.TAHUN 2017DO - 10.24843/EEB.2017.v06.i11.p06, 2017)
The ability to provide good quality of service to meet patient exspatation is a important strategy in achieving competitive advantage. Pleasant experienciae will relatives and acquaintances. This research aims to study the effect of service quality onssatisfaction and word of mouth of hospitalized patients of Hospilized Guido Valadares in Dili Timor Leste. The population of this study is all patiens who had undargone in patient at hospitalized Guido Valadares in Dili Timor Leste. The method of collecting data was porposive sampling. The number of respondents were 150 respondents. The data was analized by using path analisis. The population of this study is all patiens who had undargone in patient at hospitalized Guido Valadares in Dili Timor Leste. The method of collecting data was porposive sampling. The number of respondents were 150 respondents. The data was analized by using path analisis. The resultsof this study reveal that 1) Quality of service has positive and significant impact on satisfaction. 2) Quality of service has positive and significant impact on WOM. 3) satisfaction has positive and significant impact on WOM.